2009
DOI: 10.1002/tea.20336
|View full text |Cite
|
Sign up to set email alerts
|

Drama activities as ideational resources for primary‐grade children in urban science classrooms

Abstract: In this study we explored how dramatic enactments of scientific phenomena and concepts mediate children's learning of scientific meanings along material, social, and representational dimensions. These drama activities were part of two integrated science‐literacy units, Matter and Forest, which we developed and implemented in six urban primary‐school (grades 1st–3rd) classrooms. We examine and discuss the possibilities and challenges that arise as children and teachers engaged in scientific knowing through such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
2
26
0
5
Order By: Relevance
“…We are currently beginning a project that will examine the impacts of incorporating dramatic movement into science teaching for students in grades 3-5. Similar research has shown success in this pairing (Varelas et al, 2010 ), and we seek to replicate it on a large-scale level.…”
Section: Future Researchmentioning
confidence: 92%
“…We are currently beginning a project that will examine the impacts of incorporating dramatic movement into science teaching for students in grades 3-5. Similar research has shown success in this pairing (Varelas et al, 2010 ), and we seek to replicate it on a large-scale level.…”
Section: Future Researchmentioning
confidence: 92%
“…Contexts. In addition to design research, we are also interested in fundamental questions about culture, cognition and development, and have sought to more deeply understand the intellectual generativity (as opposed to deficits) and implicit pedagogies mobilized within everyday practices (Warren et al 2005;Barton, Tan, & Rivet, 2008;Gonzalez et al, 1995;Guti errez, Baquedano-L opez, & Tejeda, 1999;Lee, 2010;Varelas et al, 2010). For example, our research teams have studied outdoor practices of fishing, hunting, harvesting and gardening, among others.…”
Section: Studies Of Learning In Everydaymentioning
confidence: 99%
“…I presentationsdrama ges barnen rollen som publik, medan upplevelsebaserat drama innebär att de själva deltar som aktörer. När barn själva deltar, navigerar de mellan vardagliga och föreställda världar, vilket skapar ett tillstånd av dubbelt medvetande (Dorion, 2009;Varelas et al, 2010). Ett sådant tillstånd av dubbelt medvetande -metaxis -innebär att kunna växla mellan en föreställd värld (som om) och en verklig värld (som är).…”
Section: Dramatisering Och Barns Lärande I Naturvetenskapunclassified
“…Enligt Ødegaard (2003) tillåter dramatisering av vetenskap att begreppen, som hon uttrycker det, kommer till liv och införlivas i barns egna erfarenheter och livsvärldar. Varelas et al (2010) diskuterar användning av drama i relation till modellering och naturvetenskapligt lärande, och visar hur drama kan vara ett produktivt sätt för barn att närma sig abstrakta naturvetenskapliga modeller. De genomförde en studie där syftet var att stödja barn i lågstadiet att utveckla och kommunicera naturvetenskap genom drama.…”
Section: Dramatisering Och Barns Lärande I Naturvetenskapunclassified
See 1 more Smart Citation